2017
DOI: 10.3390/ijms18102061
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Isolated Syndrome According to McDonald 2010: Intrathecal IgG Synthesis Still Predictive for Conversion to Multiple Sclerosis

Abstract: While the revised McDonald criteria of 2010 allow for the diagnosis of multiple sclerosis (MS) in an earlier stage, there is still a need to identify the risk factors for conversion to MS in patients with clinically isolated syndrome (CIS). Since the latest McDonald criteria were established, the prognostic role of cerebrospinal fluid (CSF) and visual evoked potentials (VEP) in CIS patients is still poorly defined. We conducted a monocentric investigation including patients with CIS in the time from 2010 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 52 publications
(68 reference statements)
7
26
0
1
Order By: Relevance
“…In a recent study carried out by Schwenkenbecher et al, OCBs were associated with a slight increase on conversion rate to MS, but with no statistical significance. 12,17 However, in our analysis, we did not find significant differences on disease outcome associated with clinical presentation symptom, which is consistent with the results obtained in other research studies. 13,15 In our cohort 76.80% of the patients converted to MS, which is in accordance with the results obtained by a recent multicenter study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In a recent study carried out by Schwenkenbecher et al, OCBs were associated with a slight increase on conversion rate to MS, but with no statistical significance. 12,17 However, in our analysis, we did not find significant differences on disease outcome associated with clinical presentation symptom, which is consistent with the results obtained in other research studies. 13,15 In our cohort 76.80% of the patients converted to MS, which is in accordance with the results obtained by a recent multicenter study.…”
Section: Discussionsupporting
confidence: 92%
“…2). 13,17 Furthermore, the present data further underline the inverse association between age at disease onset and risk of conversion into MS. 13 Some authors suggest that clinical presentation at baseline affects MS conversion risk (with brainstem and spinal cord symptoms associated with higher conversion rates, whereas optic neuritis predicts a stable disease course). 17 In contrast, other studies showed that positive OCBs patients are at a much higher risk of converting to MS and within a shorter period of time.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Regarding results of OCB, 75% of patients with CIS have positive OCB in CSF while in RIS only 23% has positive results. These results was partially agreed with [18][19][20][21][22][23][24][25] they mentioned that, Sixty to seventy percent of patients with CIS have positive OCBs and with [26] he reported that the positive OCB were detected in 61% of patients with CIS [27]. Found CSF oligoclonal banding having sensitivity between 69-91% for diagnosis of MS.…”
Section: Discussionsupporting
confidence: 77%